CONFIRMATION OF CONFORMITY OF GOODS AS A MECHANISM FOR THE REGULATION OF INTERNATIONAL TRADE - T. Vorotyntseva (Вестник университета)
In the article the analysis of application of the mechanism of regulation of international trade to protect the market from dangerous products. In order to improve the effectiveness of the system of technical regulation and the role of the system of confirmation of conformity of goods, it is proposed to develop a Unified concept of quality control and food safety as a mechanism for regulation of international trade within the Eurasian Economic Union.